Growth and Production of Corn in Various Planting Distances Systems - Rusnadi Padjung; Muh Farid Bdr; N. Nasaruddin; Ifayanti Ridwan; Muhammad Fuad Anshori; Andi Dwie Mochammad Abduh T; Ahrani Akbar Fachri (Universitas Sembilanbelas November Kolaka, 2020)
Corn is one of the most important food commodities consumed by most people in various parts of the country. There is a real interaction between spacing varieties on the observed characters. There are one or more production chatacters that have a significant correlation with production. This research will be carried out at the Experimental Garden of the Bajeng Cereal Research Institute, Bajeng District, Gowa Regency, South Sulawesi, with a coordinate point of 5o18'21.5